2017
DOI: 10.1007/s00404-017-4509-3
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin expression features in the arcuate and anteroventral periventricular nuclei of hypothalamus of letrozole-induced polycystic ovarian syndrome in rats

Abstract: Our findings show that the number of kisspeptin-positive cells may be affected from letrozole, and that the changes in the number of these cells may be in favor of the appearance of PCOS features in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…Moreover, we found that the expression of Kiss1 mRNA and immunoreactivity were significantly increased in the ARC of both models. These results are similar to those showing an increase of Kiss1 neurons in the ARC of progesterone antagonist RU486‐induced (8) and letrozole‐induced PCOS rats (9) but are in opposition to those showing a decrease of Kiss1 neurons in the ARC of dihydrotestosterone‐induced PCOS rats (7). These findings provide solid evidence indicating possible involvement of Kiss1 neurons in the hypothalamic ARC during the development of PCOS.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Moreover, we found that the expression of Kiss1 mRNA and immunoreactivity were significantly increased in the ARC of both models. These results are similar to those showing an increase of Kiss1 neurons in the ARC of progesterone antagonist RU486‐induced (8) and letrozole‐induced PCOS rats (9) but are in opposition to those showing a decrease of Kiss1 neurons in the ARC of dihydrotestosterone‐induced PCOS rats (7). These findings provide solid evidence indicating possible involvement of Kiss1 neurons in the hypothalamic ARC during the development of PCOS.…”
Section: Discussionsupporting
confidence: 84%
“…These findings provide solid evidence indicating possible involvement of Kiss1 neurons in the hypothalamic ARC during the development of PCOS. The discrepancy observed in these independent investigations might be due to differences in the experimental approaches (e.g., rat genetic background, ages, induction drugs, and even antibodies with various specificities) (7‐9). Thus, additional data are required for clarifying the mechanism underlying PCOS development in these models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a variety of experimental animal studies have been conducted to estimate KISS1, KISS r, and KISSpositive cells in different PCOS-induced phenotypes. Aliabadi et al found that [26,27] kisspeptin-positive cells and kiss mRNA expression in letrozol-injected female rats were higher than normal rats. Additionally, they demonstrated that the enhanced neural cells in PCOS rats might contribute to the hypersecretion of LH.…”
Section: Discussionmentioning
confidence: 99%
“…15 Somatic cells exert their effects on SCs by releasing factors like GDNF and EGE2. 26 Many of possible roles for Kp on germ cells via the mentioned network are still elusive. Consistently, Kp-10 has been reported to make alterations in the rate of expression for CX43, the key junctional protein linking germ and Sertoli cells.…”
Section: Introductionmentioning
confidence: 99%